2014
DOI: 10.1097/ccm.0000000000000313
|View full text |Cite
|
Sign up to set email alerts
|

Increased Activation of the Rho-A/Rho-Kinase Pathway in the Renal Vascular System Is Responsible for the Enhanced Reactivity to Exogenous Vasopressin in Endotoxemic Rats*

Abstract: Our data suggest that activation of Rho-kinase potentiates the vascular effects of vasopressin in the kidneys, contributing to the maintenance of the hypertensive effects of this agent during septic shock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 37 publications
2
12
0
Order By: Relevance
“…Using kidneys from rats subjected to CLP -an experimental model of sepsis able to reproduce several aspects associated with human sepsis, including hypotension and systemic refractoriness to vasoconstrictors ( Supplementary Fig. S1) -we confirmed that the renal vascular bed displays a sustained reduction in the reactivity to both phenylephrine and norepinephrine after the induction of sepsis, as previously demonstrated for α 1A -adrenergic receptor agonists in experimental models of sepsis (Chen et al, 1994;Guarido et al, 2014). Most importantly, in spite of the lack of effects in control preparations, we found that at 18 h after the induction of sepsis, continuous perfusion of kidneys with the non-selective K + channel blocker tetraethylammonium was able to normalize phenylephrine-increased RVPP.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Using kidneys from rats subjected to CLP -an experimental model of sepsis able to reproduce several aspects associated with human sepsis, including hypotension and systemic refractoriness to vasoconstrictors ( Supplementary Fig. S1) -we confirmed that the renal vascular bed displays a sustained reduction in the reactivity to both phenylephrine and norepinephrine after the induction of sepsis, as previously demonstrated for α 1A -adrenergic receptor agonists in experimental models of sepsis (Chen et al, 1994;Guarido et al, 2014). Most importantly, in spite of the lack of effects in control preparations, we found that at 18 h after the induction of sepsis, continuous perfusion of kidneys with the non-selective K + channel blocker tetraethylammonium was able to normalize phenylephrine-increased RVPP.…”
Section: Discussionsupporting
confidence: 84%
“…It was previously described that exposure of in vitro blood-perfused juxtamedullary nephron preparations to endotoxin results in sustained vasoconstriction (van 5 Lambalgen et al, 1996), a finding that was reproduced in in vivo studies, revealing increased renal vascular resistance in endotoxemic animals (Lugon et al, 1989). In addition, the reactivity of the renal vascular bed in response to pressor agents in endotoxemic rats was found to be unchanged in response to norepinephrine and angiotensin II (Boffa and Arendshorst, 2005), reduced to phenylephrine (Guarido et al, 2014), and enhanced to vasopressin (Boffa and Arendshorst, 2005;Guarido et al, 2014). Together, these findings suggest that impairments in the functionality of the renal vascular bed contribute to the changes in arterial pressure during sepsis.…”
Section: Introductionmentioning
confidence: 83%
“…This is a key insight for interpreting the work by Cuarido et al (1). It may simply be the innate differences in humans versus other animals.…”
mentioning
confidence: 85%
“…I n this issue of Critical Care Medicine, Guarido et al (1) present their fascinating work in a model of endotoxemia in rats. Consistent with prior studies, they found that vasopressin could increase blood pressure in animals refractory to phenylephrine.…”
mentioning
confidence: 99%
See 1 more Smart Citation